Storytelling as a Pedagogical Strategy to Teach English Language Vocabulary to Children - Margarita del Socorro Centeno Centeno; Marling del Carmen Rivera Rugama; Lanier Roberto Sierra Herrera; Wilmer Geronimo Lagos Reyes (Revista Multi-Ensayos, 2021)
This article was written with the purpose of obtaining information from physical and digital documents, as well as, analyzing the important data used in the literature review of our project, “Storytelling as a Pedagogical Strategy to Teach English Language Vocabulary to Children”. The studies were categorized into four aspects which are ‘study’, ‘focus’, ‘context’ and ‘results. We focused our attention on gathering relevant information to achieve the objectives of this project. Since teaching English in elementary school has been recently implemented in Nicaragua, not enough research has been done in this area. We believe it is necessary to support elementary school with more research about the use of different resources to support English language teaching in this country. One of the weaknesses when learning a second language is that if children have lack of vocabulary, children will have difficulties understanding some explanations in the English language classes. Effectively teaching English will promote better communication and understanding in future English classes. Studies have proven the effectiveness storytelling has in teaching English language vocabulary to children, as well as, how storytelling can be combined with other educational instruments. Studies also found that learning vocabulary is essential to understand the assignments in the English classes and the activities in the English workbooks.